Analysis of Pollutant Transport Around a Circular Cylinder in Subcritical Regime Using Lagrangian Coherent Structures - Zheng, Xinyao; Chen, Zhizhe; Chen, Zhiyu; Chai, Lianjie; Zhang, Jiazhong (Journal of Environmental Accounting and Management, 2026)
Lagrangian coherence structures (LCSs) are introduced to study the pollutant transport process in detail, more powerful than traditional Eulerian method in describing the mass transport in transient flow. First, pollutant transport in air around a circular cylinder in the subcritical regime with Reynolds number of 140000 is numerically simulated using DES Turbulence Model. Then, the complex turbulent flow and the accompanying transport process in the cylinder wake are revealed from Lagrangian viewpoint, through the analysis of LCSs which are extracted utilizing the ridges in the finite-time Lyapunov exponent fields. Further, a comparison between flow in the laminar and subcritical regime is carried out, and the factors for the intense mixing and quasi-periodical characteristic of the subcritical regime are discovered. Finally, based on lobe dynamics, the flow field is partitioned into several regions with different physical properties, so the mass and energy transport and mixing between those regions can be precisely described and captured. The results show the application of LCSs in uncovering the structures of complex turbulent flow in environmental problems, as well as the potential of LCSs to quantitatively analyze the pollutant transport process, could provide an efficient way for the optimal control of the pollutant.